Analisis Pengaruh Harga, Pelayanan, Dan Kualitas Produk Terhadap Keputusan Pembelian Alat Elektronik Pada Toko Ardha Elektronik - Pradana, Aditya, Drs. Sujadi, M.M (2016)
In this study aims to determine individually and simultaneously the influence of price, service, and quality of products on purchase decisions in the store Ardha Electronics. In this study, the population is consumers who ever bought more than one electronic device in Ardha Electronics stores. The sampling method using purposive sampling method, sampling is done with a certain considerations, namely people who have purchased more than one product at the store Ardha Electronics. Having regard to the respondents desired to facilitate research is taken a sample of 100 people. The analytical method used in this research is by using multiple linear regression analysis and hypothesis testing by t-test, F, and the coefficient of determination. Based on the results of multiple linear regression analysis can be concluded the following research: Results of t test (partial) that the (X1), services (X2), and the quality of the product (X3) partially have a significant influence on purchasing decisions on Ardha Electronics. The result of F test (simultaneous) that the (X1), services (X2), and the quality of the product (X3) simultaneously (simultaneously) has significant influence on the purchase decisions on Ardha Electronics. Of the three independent variables that provide the most dominant influence on purchasing decisions on electronic ardha is the variable quality of the product(X3). Keywords: price, service, quality products, Purchase Decision